Measured and estimated wind speed of a stand-alone energy system with controlled bi-directional DC-DC battery bank - Ali Salam Al-Khayyat; Ahmed Kareem Abed; Amel Ahmed Ridha (Institute of Advanced Engineering and Science, 2023)
Simple control of a stand-alone variable speed wind turbine with a permanent magnet synchronous generator (PMSG) is presented in this paper. PMSG fed different types of loads by means of a converter where switched mode rectifier is connected to the PMSG, boost DC-DC converter, and voltage source inverter (VSI). The wind turbine is operated at measured wind speed and it is tested at estimated wind speed which is based on the power calculation of turbine power, generating electric power, losses power, and the dynamic power during the variation of wind speed. The estimation of wind speed would provide a scope of what a control method is applicable in practice and this would increase the performance by scheduling the connected loads. The bidirectional battery charger is controlled and used during the shortage of wind speed. The converter of the battery charger is controlled and implemented on an embedded system by using an STM32-based microcontroller. During the shortage or fluctuation of wind speed, the load voltage is controlled within the acceptable limit, where the voltage has been compensated. An extensive simulation has been conducted by MATLAB/Simulink, and the system shows a good dynamic response to the variation and decrease in wind speed.